The Importance of Studying History on individual’s awareness: A Case Study of Muslim Students in Saudi Arabia - Hasnah Alghamdi; Meguellati Achour (The Department of Islamic History and Culture in cooperation with the Center for Research and Community Service, Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2020)
The purpose of this study is to identify the effect of studying history on individual’s awareness in political and cultural aspects. The researchers sampled 315 students as respondents were determined using the snowball technique who answered the online survey developed through Google forms with an appended consent form. The survey link was sent to the student respondents via social media (WhatsApp, Emails, Messenger, and so on). These students were from Jeddah University, King Abdelaziz University, and King Saud University. Their ages ranged from 17 to 50 years. The results of this study reveal a strong, positive and significant correlation of studying history with political awareness and cultural awareness as well.